Relationships amongst chlorella isolates from the tropical, temperate and Antarctic regions based on morphological, biochemical and molecular studies / Shamala Marimuthu - Marimuthu, Shamala (2011)
Algae from the genus Chlorella are widely distributed on earth, including the Polar Regions. The alga is a model organism for physiology and biochemistry experiments as well as an important organism for biotechnological exploitation. The major objective of this study was to unravel the relationship amongst Chlorella isolates from the Antarctic, sub-Antarctic, tropical and temperate regions based on 18S rDNA sequences as well as morphological and biochemical (fatty acid profiles and pigment composition) features. Eleven isolates of Chlorella, consisting of two Antarctic isolates, one sub–Antarctic isolate, seven tropical isolates and one temperate isolate from the University of Malaya Algae Culture Collection (UMACC) were included in this study. There were no distinct morphological features that can be used to differentiate the various isolates of Chlorella studied. The pigmentation of all the strains was similar, consisting of chlorophyll a, chlorophyll b, lutein, ß-carotene, cis-neoxanthin and violaxanthin. There was no marked difference in terms of their fatty acid profile, which was dominated by 18:3. The morphology, fatty acid profiles and pigmentation of the 11 isolates showed that they belong to the “true” Chlorella. This was further supported by molecular analysis based on 18S rDNA, which revealed that they clustered together forming one clade within the Trebouxiophyceae. The phylogenetic analysis revealed that the Chlorella isolates from Antarctic were closely related to the tropical and temperate isolates.